2020
DOI: 10.3390/vaccines8030381
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Helminth Infections during Pregnancy on Vaccine Immunogenicity in Gabonese Infants

Abstract: Helminth infections are common in sub-Saharan Africa. Besides direct clinical effects, a bias towards a T helper type 2 (Th2) cell immune response is observed. The consequences of parasite infection during pregnancy for the mother and particularly for the fetus and the newborn can be severe and may include impaired immune response during acute infection and vaccination. Here, we present data of immune responses to vaccines given within the expanded program on immunization (EPI) of infants born to helminth infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…‘In-utero priming’ was first proposed in neonates born to infected mothers, who are exposed to pathogens but uninfected themselves [ 246 , 248 ]. For example, infants of helminth-infected mothers are exposed to parasite-derived products that seem to cross the placenta and potentially prime or tolerate the fetal immune response to parasite-specific as well as unrelated antigens [ 249 , 250 ]. This early exposure may have long-term effects on the child’s immune system, including their CMI to pertussis childhood vaccines [ 249 ].…”
Section: Which Factors May Affect T-cell-mediated Immunity To Pertussis Infant Vaccinations?mentioning
confidence: 99%
See 3 more Smart Citations
“…‘In-utero priming’ was first proposed in neonates born to infected mothers, who are exposed to pathogens but uninfected themselves [ 246 , 248 ]. For example, infants of helminth-infected mothers are exposed to parasite-derived products that seem to cross the placenta and potentially prime or tolerate the fetal immune response to parasite-specific as well as unrelated antigens [ 249 , 250 ]. This early exposure may have long-term effects on the child’s immune system, including their CMI to pertussis childhood vaccines [ 249 ].…”
Section: Which Factors May Affect T-cell-mediated Immunity To Pertussis Infant Vaccinations?mentioning
confidence: 99%
“…For example, infants of helminth-infected mothers are exposed to parasite-derived products that seem to cross the placenta and potentially prime or tolerate the fetal immune response to parasite-specific as well as unrelated antigens [ 249 , 250 ]. This early exposure may have long-term effects on the child’s immune system, including their CMI to pertussis childhood vaccines [ 249 ]. To date, however, there has been no robust, consistent evidence that vaccine-induced (including pertussis) immune responses of infants are strongly suppressed or affected by the helminth infection status of the mother [ 249 , 251 , 252 , 253 ].…”
Section: Which Factors May Affect T-cell-mediated Immunity To Pertussis Infant Vaccinations?mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study carried out on school-age children in rural area of Gabon showed an increased risk of P. falciparum infection due to STH in schistosomiasis-positive children [11]. Many studies have also been conducted to assess the effect of helminth infection on several commonly used vaccines [12][13][14][15][16][17][18], but little is known about their interaction with malaria vaccine candidates [19][20][21][22]. GMZ2, a malaria vaccine candidate, is a recombinant fusion protein with fragments of P. falciparum GLURP and MSP3 [23] that showed good immunogenicity when formulated with aluminum hydroxide (alum) [24][25][26] or Cationic Adjuvant Formulation 01 (CAF01) adjuvant [27].…”
Section: Introductionmentioning
confidence: 99%